PRIORITY DIRECTIONS OF THE STATE REGULATION OF COMPETITION: DOMESTIC AND FOREIGN EXPERIENCE (Economic journal of Lesya Ukrainka Volyn National University, 2019)
In the process of studying the priority directions of regulating the state of competitive relations in our state, attention is drawn to its disproportionality. This situation is due to the fact that the overwhelming majority of business structures operate in an oligopolistic market, or in general, monopoly forms of market co-operation.At the same time, a significant volume of markets at various levels continues to be monopolized, since there has still not been created identical and transparent conditions for the functioning of absolutely all market participants. That creates a number of obstacles for the development of the state's economy and ensuring an adequate level of competitive balance.It is known that today the state’s competitive policy is based on narrow-minded principles, which is insufficient for its effectiveness. As a result, the competition policy of the state in general is not investigated in the context of its macroeconomic indicators, only research of some relevant markets takes place.At present, it is important to focus attention on issues relating to world experience in combating the monopolization of power with a view to their further application on the example of Ukraine. Since, in the absence of a regulated competitive environment and without creating acceptable conditions for the coexistence of market players, its economy will not be able to function effectively.It is known that measures to implement the legislative norms of a competitive direction are the basis for the successful development of the economy of our country.Antitrust activities, including antitrust legal regulation, are a prerequisite for ensuring transparent competitive principles of coexistence of business entities.Consequently, as a result of the study of priority directions of regulation by the state of competitive relations, both in our state and in the leading countries of the world, we can sum up the following: in most countries, ensuring transparent competitive conditions of market co-operation is at a special level of control; in some states, antitrust control and its implementation is carried out by the relevant antimonopoly body (institution) under public administration.From this, we believe that domestic antimonopoly legislation needs transformation processes, and the study of the world's leading countries should contribute to this.
Keywords: regulation, state regulation, state antimonopoly policy, competition, directions of regulation of competition